The role of immunonutrition in the fight against Covid-19: an integrative review (Research, Society and Development, 2022)
The goal of this review was to carry out a search on the evidences of the role of immunonutrition in patients fighting covid-19. concerns  an integrative literature review, as search sources were the databases: Scientific Eletronic Library Online (Scielo), National Library of Medicine (PubMed), Google Scholar. For the selection of the sample, original article criteria have been established indexed between the years 2019 to 2022, the choice of this period took into account the criterion of temporality, in which the cut-off of three years was considered, as it is a recent viral disease, in English and Portuguese. The studies analyzed the possible role of nutrients, glutamine, arginine, Omega-3 and vitamin C and D in the modulation of the immune system.  It is worth to emphysize that these nutrients are directly linked to the immune response that our body releases against infections, therefore, immunonutrition is an important instrument to be used against the viral infection of covid-19. Based on the results of the articles examined, it was observed that these nutrients had a positive effect on recovery, reduction of symptoms and mortality of patients with the disease, this is due to the fact that immunonutrients play a role in reducing inflammation caused by an exacerbated response of the body to fight the virus, concomitantly with this, these immunonutrients strengthened the immune system by modulating in a balanced way the immune responses released by the body.In this way, the modulation of the immune system through nutrition has a beneficial action for the recovery of patients with Covid-19.